The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.11648/j.ajop.20180603.11
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Photoionization Cross-Section with the Position of a Hydrogenic Donor Impurity in a Gallium Arsenide Quantum Well Dot of Square Cross-Section

Abstract: In the present work, a theoretical study of the variation of the photoionization cross-section with the incident photon frequency and the axial position of a hydrogenic donor impurity in GaAs quantum well dot of square cross-section is carried out. In the calculation, a trial wave function in the effective mass approximation and a finite potential well is used. The wave function is constructed with an appropriate envelope wave function that satisfies the boundary conditions, i.e., the wave function vanishes at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Winnie Otieno et al showed that the cross section of photoionization in quantum wells is sensitive to the location of the impurity and the frequency of the incident photons [6]. In particular, Zorkani et al [7] studied the computation of the cross section of photoionization taking into account the carrier interaction load -phonon as well as the central correction by means of an analytical potential of impurity proposed by Munnix et al [8] in the case of gallium arsenide doped with manganese.…”
Section: Introductionmentioning
confidence: 99%
“…Winnie Otieno et al showed that the cross section of photoionization in quantum wells is sensitive to the location of the impurity and the frequency of the incident photons [6]. In particular, Zorkani et al [7] studied the computation of the cross section of photoionization taking into account the carrier interaction load -phonon as well as the central correction by means of an analytical potential of impurity proposed by Munnix et al [8] in the case of gallium arsenide doped with manganese.…”
Section: Introductionmentioning
confidence: 99%